THE UTILIZATION OF COFFE PASSES AS TEXTILE DYES WITH DYNING BACKGROUND TECHNIQUES - Taufik Yahya, Prebiestian; Darwoto, Darwoto (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2021)
This design was carried out as a form of experimental development of natural coloring using coffee grounds waste with the tie-dye technique offering a unique and attractive visual. The purpose of this design is to develop textile dyeing with coffee waste by giving geometric patterns through the tie-dye technique with a variety of fixators that produce different color reactions in a visual work in plain cloth which is given a motif through the design process. The results of this textile design are as follows: (1) Coffee grounds as a natural textile dye through tie-dye technique with a source of geometric line ideas in tie-dye design. The design results succeeded in making 6 textile designs. (2) The application of coffee dregs staining with the tie-dye technique in the form of lines and using several fixators with different color reactions produces a product that looks attractive, elegant, striking, has distinctive features and is different from the others.